Comparative study of analgesic effect of breastfeeding and oral sucrose in full-term newborns - Patel, Saurabh Kumar; Gajbhiye, Milnd; Singh, Jyoti; Singh, H P (Indian Journal of Child Health, 2016)
Objective: To study the effects of breastfeeding (BF) and oral sucrose solution on pain due to intramuscular injection in newborns. Design: A prospective, interventional, randomized control study. Setting: Tertiary care hospital. Participants: Randomly selected 150 full-term vaginally delivered healthy newborns. Intervention: A total of 150 newborn infants were randomly divided into three groups. Out of 150 neonates, 50 were included in Group I as control group; 50 were included in Group II as intervention, in which 1 ml of 25% oral sucrose solution was given 2 min before the vaccination; 50 neonates were included in Group III as intervention group, in which BF started 2 min before vaccination and continued until the end of injection. Outcome Measure: The primary outcome of the study was to assess pain by premature infant pain profile (PIPP) score. Secondary outcome measured was changed in heart rate (HR), oxygen saturation (SpO2), and crying time. Results: Mean PIPP scores were lower in the BF group (8.36) than in the sucrose solution group (11.06), and difference was significant (p<0.0001). The mean difference in the increase in HR, decrease in SpO2, and total duration of cry for the breastfeeding group were 13.47, 2.33, and 23.8, respectively, and for sucrose group, they were 16.58, 2.07, and 26.36, respectively (p>0.05). Conclusion: BF and oral sucrose both are equally efficacious in reducing crying time and physiological parameters (HR, SpO2) after intramuscular injection in neonatal period but desaturation was more observed in oral sucrose solution. Further, PIPP score is less in BF group. Thus, BF provides superior analgesia to oral sucrose in term newborns.